2015
DOI: 10.1039/c5ra05437k
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous NaYF4:Yb,Er@Au–Pt(iv)-FA nanospheres for dual-modal imaging and synergistic photothermal/chemo-anti-cancer therapy

Abstract: Mesoporous NaYF4:Yb,Er@Au–Pt(iv)-FA up-conversion nanoparticles have been designed for dual-modal imaging-guided anti-cancer therapy, and show excellent inhibition toward cancer cells due to the synergistic photothermal/chemo-therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…10 For the first step, the intermediate product of c,c,t-Pt(NH 3 ) 2 Cl 2 (OH) 2 was prepared according to the literature with slight modification. 10,38 Briefly, cisplatin (Pt(NH 3 ) 2 Cl 2 , 2.00 g, 6.67 mmol) and H 2 O 2 (30 wt%, 11.37 mL, 100.0 mmol) were dissolved in H 2 O (90 mL, pH = 7) and the reaction mixture was heated to 70 °C with magnetic stirring for 5 h in a dark chamber. The mixture was then cooled and stirring was continued overnight.…”
Section: Synthesis Process Of the Pt(iv) Prodrugmentioning
confidence: 99%
See 1 more Smart Citation
“…10 For the first step, the intermediate product of c,c,t-Pt(NH 3 ) 2 Cl 2 (OH) 2 was prepared according to the literature with slight modification. 10,38 Briefly, cisplatin (Pt(NH 3 ) 2 Cl 2 , 2.00 g, 6.67 mmol) and H 2 O 2 (30 wt%, 11.37 mL, 100.0 mmol) were dissolved in H 2 O (90 mL, pH = 7) and the reaction mixture was heated to 70 °C with magnetic stirring for 5 h in a dark chamber. The mixture was then cooled and stirring was continued overnight.…”
Section: Synthesis Process Of the Pt(iv) Prodrugmentioning
confidence: 99%
“…The platinum(IV) prodrug c,c,t-Pt(NH 3 ) 2 Cl 2 (OOCCH 2 CH 2 -COOH) 2 was synthesized according to a literature method 10,38 (Scheme 1) and the structures of the intermediate product (c,c,t-Pt(NH 3 ) 2 Cl 2 (OH) 2 ) and the Pt(IV) prodrug c,c,t-Pt(NH 3 ) 2 Cl 2 (OOCCH 2 CH 2 COOH) 2 were confirmed by ESI-MS and FT-IR (Fig. S1 and S2, ESI †).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Onto the surface of the PAA/PAMAM-functionalized NYF NRs, presynthesized spherical Au nanocrystals with an average diameter of 24.8 ± 3.1 nm (Au SNCs, Figure S3) were anchored, yielding NYF NR–Au SNC core–satellite nanostructures, in which the Au SNCs are uniformly attached to the surface of the functionalized NYF NRs (NYF–Au sat CStNs, Figures c,g and S4). The uniform assembly of the Au SNCs onto the NYF NRs, which has been challenging so far, could be realized by the ligand (poly­(vinyl alcohol), PVA) treatment of the Au SNCs before the assembly process and the moderate temperature of the reaction solution (50 °C). Without the PVA passivation of the Au SNCs, severe aggregation of the Au SNCs was observed during the process (Figure S5a).…”
Section: Resultsmentioning
confidence: 99%
“…In the past 10 years, light absorbing nano-agents of Cu x S y nanoparticles and Au nanoclusters were combined with upconversion NPs, forming numbers of multifunctional cancer therapy platforms, such as NaGdF 4 :Yb,Er@ NaGdF 4 :Yb@NaNdF 4 :Yb@mSiO 2 -Au 25 , Y 2 O 3 :Yb,Er@Y 2 O 3 :Yb@ mSiO 2 -Au 25 -P(NIPAM-MAA) and NaYF 4 :Yb,Er@Au-Pt(IV)-FA nanocomposite spheres and Y 2 O 3 :Yb,Er@mSiO 2 -Cu x S doubleshelled hollow spheres. [197][198][199][200][201][202] Firstly, the upconversion luminescence process in these platforms was utilized to take advantage of the strengthening of the photothermal effects by the fluorescence resonance energy transfer (FRET) effect. All the results showed that these therapy platforms have considerable thermal effect to kill tumors directly.…”
Section: Light Responsive Drug Deliverymentioning
confidence: 99%